2022
DOI: 10.3389/fpubh.2022.829674
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Trends in Mental Health Problems Among Urban Chinese Adolescents: Results From Repeated Cross-Sectional Data in Changsha 2016–2020

Abstract: This study performed a repeated cross-sectional analysis to explore possible trends in mental health problems among Chinese adolescents over the years of 2016–2020. A total of 2,837 different seventh-grade students were surveyed in three waves from a junior high school in Changsha city, Hunan province in China (978 in 2016, 949 in 2019, and 910 in 2020) using the Mental Health Inventory of Middle School Students (MMHI-60). The results showed that obsessive-compulsive tendencies, interpersonal sensitivity, depr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…Over the 22‐year period, boys' scores remained relatively stable, whereas girls' scores inclined; there was an approximately two‐fold increase in the gender gap. These results are consistent with our previous cross‐cohort comparisons (Slobodskaya et al., 2023) and some, but not all, studies from high‐income western countries (Collishaw & Sellers, 2020; Fink et al., 2015; van Vuuren et al., 2018) and China (Wu et al., 2022). It is notable that girls' emotional symptoms and internalizing problems showed a steeper incline since 2007–2008.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Over the 22‐year period, boys' scores remained relatively stable, whereas girls' scores inclined; there was an approximately two‐fold increase in the gender gap. These results are consistent with our previous cross‐cohort comparisons (Slobodskaya et al., 2023) and some, but not all, studies from high‐income western countries (Collishaw & Sellers, 2020; Fink et al., 2015; van Vuuren et al., 2018) and China (Wu et al., 2022). It is notable that girls' emotional symptoms and internalizing problems showed a steeper incline since 2007–2008.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence from lower-income countries which often experience more rapid social change, is not entirely consistent. In line with much adolescent research, one study of 2837 seventh grade students from one high school in China found an increase in emotional problems among girls and no change among boys from 2016 to 2020 (Wu et al, 2022). However, a cross-temporal metaanalysis of 48 studies of Chinese adolescents showed that depression symptoms increased among boys and did not change among girls from 1989 to 2018 (Su & Liu, 2020).…”
Section: Cross-country Variation Of Time Trends In Adolescent Mental ...mentioning
confidence: 81%
“…The results of the current study show that male college students have signi cantly higher levels of interpersonal sensitivity than female college students, about which existing studies have come to con icting conclusions. Some studies believe that there is no difference between males and females in interpersonal sensitivity (Boyce & Parker, 1989;Guo et al, 2022), while the study of adolescent mental health noted a signi cantly higher incidence of psychological problems in females than in males, including interpersonal sensitivity (Wu et al, 2022). The study of interpersonal sensitivity among undergraduate students during the epidemic period is consistent with our conclusion, which may be due to the in uence of personality characteristics, social environment and cultural background.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, one study using a state-clustering algorithm suggested that the females’ brain networks switch connectivity states less frequently than the males’ and can thus be considered more stable over time [ 43 ]; in another study using the temporal clustering coefficient, it was found that the females’ brain networks are more stable than the males’ and such differences are significant at both the global and regional (particularly within the default-mode and subcortical regions) levels [ 14 ]. These findings may not only highlight the necessity to control for sex effects in dFC studies, but also provide valuable insight into the sex differences in clinical characteristics of many mental problems and disorders (e.g., females are more likely to be affected by depression) [ 48 , 49 , 50 ].…”
Section: Possible Influencing Factors When Analyzing the Temporal Sta...mentioning
confidence: 99%